(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The article is devoted to the study of syntactic language play techniques in humorous discourse, since the phenomenon of language play is closely connected with this type of discourse. The notions of humorous discourse and language play are considered. Humorous discourse is based on the principle of transmission of a humorous message from the addresser to the addressee. The purpose of this message is to get away from a serious conversation, reduce the social distance between the conversation participants and form friendly interrelationship. Communicative intension and humorous tonality are key components of humorous discourse. Language play means intentional violation of the rules of the language in order to achieve a humorous effect. Language play exists at all levels of language structure: phonological, morphological, lexical and syntactic. The article is based on the material of a popular American sitcom “Scrubs” dedicated to the everyday life of doctors. Сases of usage syntactic language play in the speech of six characters of the sitcom (John Dorian, Percival Cox, Christofer Turk, Elliot Rid, Carla Espinoza and Jordan Sullivan) are considered. In their jokes, characters in the majority of cases use lexical language play techniques, but syntactic language play is also quite common. The most frequently used syntactic means (repetition, parcellation, rhetorical questions, tautology, zeugma) are determined. Specific cases of usage language game techniques at the syntactic level are presented.